ECAP‐Controlled Closed‐Loop Spinal Cord Stimulation Efficacy and Opioid Reduction Over 24‐Months: Final Results of the Prospective, Multicenter, Open‐Label Avalon Study. Issue 6 (2nd May 2021) - Brooker, Charles; Russo, Marc; Cousins, Michael J.; Taylor, Nathan; Holford, Lewis; Martin, Rebecca; Boesel, Tillman; Sullivan, Richard; Hanson, Erin; Gmel, Gerrit Eduard; Shariati, Nastaran Hesam; Poree, Lawrence; et al.
Abstract: Introduction: Chronic pain is a major public health concern, as is the associated use of opioid medications, highlighting the importance of alternative treatments, such as spinal cord stimulation (SCS). Here, we present the final 24‐month results of the Avalon study, which investigated the use of the first closed‐loop SCS system in patients with chronic pain. The system measures the evoked compound action potentials (ECAPs) elicited by each stimulus pulse and drives a feedback loop to maintain the ECAP amplitude near constant. Methods: Fifty patients were implanted with the Evoke system (Saluda Medical) and followed over 24‐months. Pain, quality of life (QOL), function, sleep, and medication use were collected at baseline and each scheduled visit. ECAP amplitudes and programming adjustments were also monitored. Results: At 24 months, responder rates (≥ 50% pain reduction) and high responder rates (≥ 80% pain reduction) for overall pain were 89.5% and 68.4%, respectively, the latter up from 42.2% at 3 months. Significant improvements from baseline were observed in QOL, function, and sleep over the 24 months, including ≥ 80% experiencing a minimally important difference in QOL and > 50% experiencing a clinically significant improvement in sleep. At 24 months, 82.8% of patients with baseline opioid use eliminated or reduced their opioid intake. Over the course of the study, reprogramming need fell to an average of less than once a year. Conclusion: Over a 24‐month period, the Evoke closed‐loop SCS maintained its therapeutic efficacy despite a marked reduction in opioid use and steady decrease in the need for reprogramming.